Biodistribution of Tc-99m Labeled Isoniazid Solid Lipid Nanoparticles in Wistar Rats - Ghazizadeh, Fereshteh (Iran J Pharm Res, 2018)
In this study Isoniazid (INH) as one of the first line drugs in treatment of Tuberculosis was investigated to be loaded in Solid Lipid Nanoparticles (SLNs) for reducing hepatotoxicity as well as prolonging drug release. High shear homogenization method was performed to prepare INH SLNs. To compare biodistribution of INH before and after loading in SLNs, INH was labeled by Technetium 99 (Tc99) after derivatization. The particle size of the prepared SLNs was 167 and 200 nm before and after lyophilization, respectively. Loading efficiency was calculated using the reverse method and release study was performed by using the dialysis sack method. Loading efficiency was 98%, and more than 85% of the loaded drug released in 3 h. Differential Scanning calorimeter (DSC) studies were performed for evaluating of the probability of happening hydrogen bonds or other chemical interactions between cholesterol as carrier and isoniazid as active pharmaceutical ingredient. The results could support the probability of hydrogen bond formation between cholesterol and INH. Gamma Scintigraphy studies showed that after administering INH SLNs, longer drug retention in the body was obtained compared to free INH. Quantitative gamma counting showed that the concentration of INH in the liver and intestines could be decreased by using nanotechnology.